Remediation of Condemn Oil Polluted Loamy Soil Using Azadirachta Indica (Neem) - Wecheonwu Bright Chinyeze; Nwachukwu Kizito Chibuike (International Journal of Climate Conditions, 2024)
The remediation of condemn oil polluted loamy soil using neem (azadirachta indica) was investigated. The neem leaves came from Akpugo in the southeast Nigerian state of Enugu State's Nkanu West local government area. The leaves were dried at room temperature and subjected to grinding machine to obtain the powdered form of the dried leaves that serve as treatment to remediate condemn oil polluted loamy soil. Three masses 5g, 10g and 15g of the powdered Azadirachta indica were measured in the ratio of 1:2:3 respectively and added in the mixtures. The analysis for characterization of individual hydrocarbons in the condemn oil and the mixture of soil, azadirachta indica and condemn oil were carried out. The concentration of the first members of the three families n-octane (C8), n-icosane (C20) and n-triacontane (C30) identified were determined weekly for three weeks cure. The plot of concentration of total petroleum hydrocarbon (TPH) against time rapidly decreased in the concentrations of the first members of the three families’ n-octane, n-icosane and n- triacontane with respect to time in days in the increasing order of masses azadirachta indica as 5g  10g  15g and the plot of concentration of total petroleum hydrocarbon (TPH) against the masses of azadirachta indica there was rapid decrease of the concentration of (TPH) with the masses of azadirachta indica in increasing order of time as 7days  14days  21. From the result obtained the following recommendations were made: Neem is recommended for remediation of condemn oil and related products in loamy soil and other soil environment in general, government at all level should establish plant for the manufacturing of neem powder and neem is recommended to all oil companies for oil spillage control.
Keywords: Condemn Oil; Environment and Azadirachta Indica; Hydrocarbon Degradation; Polluted Soil; remediation